Global Kamasan - Siobhan Campbell (Pusat Kajian Bali Universitas Udayana, 2011)
AbstractThe painting tradition of Kamasan is often cited as an example of theresilience of traditional Balinese culture in the face of globalisation andthe emergence of new forms of art and material culture. This articleexplores the painting tradition of Kamasan village in East Bali and it’srelationship to the collecting of Balinese art. While Kamasan paintingretains important social and religious functions in local culture, thevillage has a history of interactions between global and local playerswhich has resulted in paintings moving beyond Kamasan to circulate invarious locations around Bali and the world. Rather than contribute to thedemise of a local religious or cultural practice, exploring the circulation ofpaintings and the relationship between producers and collectors revealsthe nuanced interplay of local and global which characterises the ongoingtransformations in traditional cultural practice.